Analisis Pengaruh Penerapan Health Facilities Information System (H.F.I.S) Terhadap Kinerja Karyawan Rsud Meuraxa Kota Banda Aceh - Ahmad, Adi; Azzuma, Deefri; Imilda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
An effort to speed up and simplify the collaboration process between BPJS Health and Health Facilities is by providing the Health Facilities Information System (H.F.I.S.) Application. This HFIS application is an application that can be used by all prospective health facilities that will collaborate with BPJS Health. However, the ability of each user is different in learning or mastering the application system. Thus, the level of perceived understanding will vary when the application is implemented by the user. Therefore, the author tries to analyze the level of user understanding when interacting with the system, which in this case is HFIS. The analysis was carried out using the usability method as a method used to assess the level of human understanding when using a tool or other man-made object to achieve certain goals. The aims of this research are; to analyze the results of implementing the HFIS application system and to analyze the user's capabilities regarding the HFIS application based on benchmarks from usability indicators. This research was conducted using a quantitative analysis approach. The data obtained directly is the result of interviews and questionnaires with HFIS application users.